Productive performance of Canchim and Nellore females. IV. Second calving - Alencar, Maurício Mello de; Bugner, Manfred (Pesquisa Agropecuaria Brasileira, 2014)
First calving interval and, age and weight at second calving of 57 Canchim and 57 Nellore cows, raised on pasture in the state of São Paulo, Brazil, were studied. The analyses of variance indicated no effects of calf sex on calving intervals and age at second calving. Season of the previous calving had no effect on calving interval, but significantly affected (P < 0.01) age at second calving, as a consequence of age at first calving. Cows that calved during the rainy-season (November to April) showed lower age at second calving. The breed x season of calving interaction affected significantly (P < 0.05) weight at second calving, and the Canchim cows were heavier than the Nellore ones. There was no difference between the calving intervals of me Canchini (441 days) and Nellore (418 days) cows. The age at second calving was lower (P < 0.10) for Canchim (1,620 days) than for Nellore (1,668 days) cows, as a consequence of the lower age at first calving of the Canchim females.